Online state and unknown inputs estimation for nonlinear systems with particle filter based recursive expectation‐maximization algorithm - Liu, Zhuangyu; Zhao, Shunyi; Wan, Haiying; Luan, Xiaoli; Liu, Fei (International journal of robust and nonlinear control, 2024)
The article presents an innovative approach to simultaneously estimate states and unknown inputs (UIs) in nonlinear systems using a particle filter (PF) based recursive expectation‐maximization (EM) algorithm. This method is distinct from traditional iterative EM algorithms. During the E‐step, it calculates the Q‐function recursively within the maximum likelihood framework, while the PF estimates the system states. The M‐step involves local maximization of the recursive Q‐function to online estimate the UIs. The effectiveness of the PF‐based recursive EM algorithm is demonstrated with a numerical example, and comparisons with the augmented state PF are made to highlight its advantages. Finally, the proposed algorithm is implemented in a real application for the estimation of the continuous fermentation process.